2013
DOI: 10.1007/s00125-013-2986-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of modified LDL and HDL on retinal pigment epithelial cells: a role in diabetic retinopathy?

Abstract: Aims/hypothesis Blood–retina barrier leakage in diabetes results in extravasation of plasma lipoproteins. Intra-retinal modified LDL have been implicated in diabetic retinopathy (DR), but their effects on retinal pigment epithelial (RPE) cells and the added effects of extravasated modified HDL are unknown. Methods In human retinas from individuals with and without diabetes and DR, immunohistochemistry was used to detect ApoB, ApoA1 and endoplasmic reticulum (ER) stress markers. In cell culture, human RPE cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 47 publications
8
73
2
2
Order By: Relevance
“…Consistent with a general neurovascular retinal insult in DR ( 18 ), we also found evidence of a broad array of cytotoxic effects: "highly oxidized, glycated LDL" promoted oxidative stress, endoplasmic reticulum (ER) stress, infl ammation and abnormal gene expression, and decreased viability, not only in retinal vascular cells (endothelial cells, pericytes), but also in Müller glia and retinal pigment epithelial cells (RPEs) (9)(10)(11)(12)(13)(14)(15).…”
Section: Flow Cytometry For Cell Surface Receptorssupporting
confidence: 70%
See 1 more Smart Citation
“…Consistent with a general neurovascular retinal insult in DR ( 18 ), we also found evidence of a broad array of cytotoxic effects: "highly oxidized, glycated LDL" promoted oxidative stress, endoplasmic reticulum (ER) stress, infl ammation and abnormal gene expression, and decreased viability, not only in retinal vascular cells (endothelial cells, pericytes), but also in Müller glia and retinal pigment epithelial cells (RPEs) (9)(10)(11)(12)(13)(14)(15).…”
Section: Flow Cytometry For Cell Surface Receptorssupporting
confidence: 70%
“…In brief, pericytes were trypsinized, washed twice with cold disease ( 7 ). We therefore hypothesized that the dominant effects of lipoproteins in DR occur not in plasma, but rather after extravasation through leaking blood-retina barriers (BRBs) (8)(9)(10)(11)(12)(13)(14)(15); the extent of this leakage may be more important than plasma concentrations of lipoproteins. We further hypothesized that extravasated intra-retinal lipoproteins undergo extensive modification (glycation, oxidation), rendering them cytotoxic ( 8 ).…”
Section: Flow Cytometry For Cell Surface Receptorsmentioning
confidence: 99%
“…In a study of the prevalence of and risk factors for diabetic retinopathy in people with newly diagnosed type 2 diabetes mellitus using Scottish national data, diabetic retinopathy was associated with male sex, systolic blood pressure, time to screening and obesity [27]. In terms of dyslipidaemia, intraretinal modified LDLs have been implicated in diabetic retinopathy, and it has been shown that extravascular modified LDLs may promote retinal pigment epithelium injury through oxidative stress, endoplasmic reticulum autophagy and apoptosis, whereas modified HDLcholesterol had protective effects [28,29]. The same holds true for other novel risk markers such as serum apolipoprotein AI [30].…”
Section: Discussionmentioning
confidence: 99%
“…-Inflammation -Oxidative stress -Blood clotting -Fibrosis -Cytotoxicity -Pro-and anti-angiogenic actions -Effects on cell-signaling and molecular pathways AGE-based modification of circulating proteins and extravasated proteins such as LDL enhances their pathogenicity, also in the retina (reviewed in [162][163][164][165][166][167]). In the DCCT/EDIC cohort, we demonstrated that baseline levels of AGE-LDL and oxidized LDL (oxLDL) within circulating immune complexes were independent predictors for retinopathy progression several years later [26].…”
Section: Factors Related To Advanced Glycation Endproducts (Ages)mentioning
confidence: 99%
“…Lyons' team has shown that extravasated and modified LDL and immune-complexed oxLDL are present in the retina of diabetic patients. They have also demonstrated that glycated LDL and/or oxLDL exert cytotoxicity to cultured human retinal capillary endothelial cells [192], pericytes [166,[192][193][194][195], retinal pigment epithelium [165], and Muller glial cells [196]. Finally, these glycated LDL could be shown to cause changes in cell signaling, gene expression, cell apoptosis, and autophagy [165,192,193,195,196].…”
Section: Lipid-and Lipoprotein-related Biomarkersmentioning
confidence: 99%